2020
DOI: 10.1007/s00105-020-04660-w
|View full text |Cite
|
Sign up to set email alerts
|

Externe wissenschaftliche Evaluation der ersten Teledermatologie-App ohne direkten Patientenkontakt in Deutschland („Online Hautarzt – AppDoc“)

Abstract: Zusammenfassung Hintergrund Die Teledermatologie adressiert das Problem des Fachärztemangels und der oft langen Wartezeit auf einen Termin beim Dermatologen. Das Modellprojekt „Online Hautarzt – AppDoc“ ermöglicht eine schnelle anonyme fachärztliche Begutachtung und wurde am 22.10.2018 von der Landesärztekammer Baden-Württemberg als Modellprojekt für 2 Jahre genehmigt. Ziel der Arbeit (Fragestellung) Das Ziel der vorliegenden Arbeit ist die Präsentation der ersten realen Versorgungsdaten für die deutsche Te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 17 publications
(24 reference statements)
1
6
0
1
Order By: Relevance
“…In summary, the S&F application showed good feasibility, satisfaction, and acceptability while improving patients' health status. Similar to our results (85.1% solved requests), Lindemann et al 3 found therapeutic efficiency in 83.3% of patients, whereas Sondermann et al 4 stated that a diagnosis was possible in 90.3% of cases. Concerning the latter, 35.7% of patients were still recommended to see a physician in-person (21.3% in our study) and only 46.9% of patients received a therapy recommendation (71.0% in our study).…”
supporting
confidence: 91%
“…In summary, the S&F application showed good feasibility, satisfaction, and acceptability while improving patients' health status. Similar to our results (85.1% solved requests), Lindemann et al 3 found therapeutic efficiency in 83.3% of patients, whereas Sondermann et al 4 stated that a diagnosis was possible in 90.3% of cases. Concerning the latter, 35.7% of patients were still recommended to see a physician in-person (21.3% in our study) and only 46.9% of patients received a therapy recommendation (71.0% in our study).…”
supporting
confidence: 91%
“…Nine reviews [22][23][24][25][28][29][30]36,38] and one systematic review [32]; • Twenty-five papers [21,26,27,31,[33][34][35][40][41][42][43][44][45]48,[50][51][52][53][54][55][56][57][58][59][60].…”
Section: Resultsmentioning
confidence: 99%
“…The search provided 40 components [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] in the three years since the COVID-19 pandemic outbreak (at the date of this study).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations